KONSEP DESAIN PENATAAN RUANG SERVIS PADA RUMAH SUSUN SEDERHANA SEWA BERLANDASKAN HASIL EVALUASI PURNA HUNI - M Musyawaroh; Murtanti Jani Rahayu (Diponegoro University, 2012)
This study aims, formulate design of Rusunawa service space based on Post Occupancy Evaluation.The approach used in this study is qualitative rationalistic, that emphasize the empiri meaning, intellectual understanding and the ability to maintains logic supported by relevant empirical data. Object of research is Rusunawa in Surakarta and its surroundings. Samples studied are a group of Services space in Rusunawa, consisting of individual service each unit house : Kitchen, warehouse / storage, KM / WC, wash dishes, wash clothes, the clothes drying. And communal service space consisting of: landfills, parking lots. The sampling technique is porpusive of maximum variation, that means taking a sample that has information about the service space. Model Rusunawa service space designed based on the type of occupant activities, evaluation / assessment of the best performance of each service spac, the best perception of occupants indicated by behavioral responses, an ideal precedent servicing space obtained from results of field surveys, comparative studies and standards or the basic criteria design of service space Rusunawa.